The Inhomogeneous Distribution of Tritium and Radiocarbon in the Abyssal Southern Ocean - 陳鎮東(Chen-Tung A. Chen); Michael R. Rodman (TAO : Terrestrial, atmospheric, and oceanic sciences, 1990)
The tritium and radiocarbon measurements taken at the Southern Ocean GEOSECS stations were analyzed. Excess CO2 for the Atlantic GEOSECS stations 76, 77, 82, 85, 87, 89, 91 and for all the atations of the SOMOV-81 cruise were correlated with the radiotracer data. Radiocarbon and excess CO2 support the tritium data showing that these tracers are not homogeneously distributed in the deep-water column. The preformed radiocarbon value of the Antarctic Surface water component in the Antarctic Bottom Water was estimated to be -- 139.3 x 10^-3.